392 Maintenance olaparib in patients with newly diagnosed advanced ovarian cancer and a BRCA mutation: subgroup analysis by risk in the phase III solo1 study. (4th December 2020) - Colombo, Nicoletta; Bradley, William; Moore, Kathleen; González-Martín, Antonio; Scambia, Giovanni; Oaknin, Ana; Friedlander, Michael; Lowe, Elizabeth; Rowe, Phil; Disilvestro, Paul
Abstract : Introduction/Background: In the Phase III SOLO1 study (NCT01844986 ) of patients with newly diagnosed advanced ovarian cancer and a BRCA mutation (BRCAm), maintenance olaparib significantly improved investigator-assessed progression-free survival (PFS) versus placebo (hazard ratio [HR] 0.30, 95% CI 0.23–0.41; P<0.001; Moore et al. N Engl J Med 2018). We present an exploratory analysis from higher-risk and lower-risk subgroups. Methodology: Patients received olaparib 300 mg twice daily or placebo for up to 2 years or until disease progression. In this exploratory analysis (primary data cut-off: 17 May 2018), patients in the higher-risk group had stage IV disease, stage III disease with residual disease following primary debulking surgery, inoperable stage III disease, or had stage III disease and underwent interval surgery. Patients in the lower-risk group had stage III disease without residual disease following primary debulking surgery. PFS was assessed by investigators and blinded independent central review (BICR). Response was assessed using modified RECIST v1.1. Results: Of 391 patients, 56% were higher risk and 44% were lower risk. After a median follow-up overall of ~41 months, the risk of disease progression/death per investigator was significantly reduced with olaparib versus placebo in the higher-risk group (HR 0.34, 95% CI 0.24–0.48; 66% reduction) and the lower-risk group (HR 0.33, 95% CI 0.20–0.52; 67% reduction) (figure 1 ). Investigator-assessed median PFS was 39.0 versus 11.1 months for olaparib versus placebo, respectively in the higher-risk group, and not reached (NR) versus 21.9 months in the lower-risk group (figure 1 ). Results were similar per BICR (table 1 ). Conclusion: In this exploratory analysis of data from the SOLO1 study, maintenance olaparib provided a substantial PFS benefit over placebo in patients with both higher-risk and lower-risk newly diagnosed advanced ovarian cancer and a BRCAm, with an investigator-assessed median PFS of 39 months and NR with olaparib treatment in higher-risk and lower-risk groups respectively after a median follow-up of ~41 months. SOLO1 is the only trial of maintenance monotherapy with a PARP inhibitor to have demonstrated a consistently high reduction in the risk of progression/death in both higher-risk and lower-risk patients with newly diagnosed advanced ovarian cancer. Disclosures: Nicoletta Colombo: Consulting fees or advisory role from Roche/Genentech, PharmaMar, AstraZeneca, Clovis Oncology, Pfizer, MSD Oncology, Takeda, Tesaro, BioCad and GlaxoSmithKline; honoraria from Roche/Genentech, AstraZeneca, Tesaro and PharmaMar. William Bradley: Nothing to disclose. Kathleen Moore: Advisory board fees from Advaxis, Aravive, AstraZeneca, Clovis, Eisai, Genentech/Roche, Immunogen, Janssen, Merck, Oncomed, Pfizer, Samumed, Tesaro, VBL Therapeutics. Antonio González-Martín: Speaker role/consulting fees from AstraZeneca, PharmaMar, Roche, Tesaro; consulting fees from Clovis Oncology, Genmab, Inmunogen, MSD, Pfizer. Giovanni Scambia: Nothing to disclose. Ana Oaknin: Consulting fees from AstraZeneca, Clovis Oncology, Genmab, Immunogen, PharmaMar, Roche, Tesaro. Michael Friedlander: Honoraria and speaker role/advisory boards from AstraZeneca; advisory board fees from Lilly, MSD, Takeda, Novartis; non-remunerated consulting for AbbVie; research funding from Beigene, AstraZeneca, Novartis. Elizabeth S. Lowe: Shareholder and employee of AstraZeneca. Philip Rowe: Shareholder and employee of AstraZeneca. Paul DiSilvestro: Consulting fees from AstraZeneca, Tesaro.